The Impact of Augmented Reality (Ar) on Vocabulary Acquisition in Elementary School Students - Asfinatu Nurjanah (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
Vocabulary development is one of the key areas in learning English as a second/foreign language, especially for children. New technologies, including Augmented Reality (AR), provide an interactive and immersive learning environment which can enhance vocabulary retention in a more engaging way. Despite increasing interest, studies on long-term effects and AR application in elementary education are still scarce. The purpose of this research is to analyze the effect of AR on English vocabulary knowledge of elementary school students. A quasi-experimental one-group pre-test and post-test were undertaken with a sample of 25 fifth grade students of SDN Jambon 2-Yogyakarta. Data was collected through vocabulary proficiency tests of CEFR A1–A2 levels and student perception questionnaires derived from established instruments. Descriptives and inferential statistical analyses were utilised – (paired sample t-tests and the calculation of effect sizes). The pre-test data showed that students’ mean scores of vocabulary were in the category of “Fair” (M = 61.56), as most participants encountered difficulties in pronunciation, spelling, meaning interpretation, and contextual usage. The average posttest score rose significantly to 83.20 in the “Proficient” rank after the AR intervention phase. The change was statistically significant (p = 0.000, t = 8.996), which indicated that AR had a significant positive effect on vocabulary learning. Findings indicate that vocabulary learning is positively influenced by AR-supported learning experience, providing students with a dynamic and joyful learning space. The research highlights AR’s promise as a pedagogical medium in elementary level English education, with empirical evidence for its implementation in technology-enhanced language learning.